Factors Affecting Physical Self-Care Among Patients with Tuberculosis - dwidiyanti, Meidiana; Sari, Sri Padma; Wijayanti, Diyan Yuli; Ningsih, Hasanah Eka Wahyu (Jurnal Keperawatan Soedirman, 2019)
Background physical self-care is necessary to gain patient involvement in health care in order to improve health outcome among tuberculosis patients. However, Factors related to support of physical self-care among patient tuberculosis under treatment was very rarely considered. This study aimed to identify the correlation between coping strategy, self-care management process and family well-being as factors associated with physical self-care. Method: A correlation study was conducted among forty-five of tuberculosis patients using purposive sampling. Data were collected within follow up session after implementing self-management support intervention by using physical self-care, coping strategy, self-care management process and family well-being questionnaire. Pearson test was used to analyze the data. Result: There were a significant association between self-care management process (r= 0.590; p=0.000), family well-being (children) (r=0.331; p=0.000) and physical self-care. However, there were no relationship between family well-being (parent) (p=0.789), coping strategy (p=0.874) and physical self-care among tuberculosis patient. Conclusion: Self-care management process and family well-being on children are essential factors to improve physical self-care among tuberculosis patient. Therefore, intervention which integrate those factors are important to enhance physical self-care among patients with tuberculosis